SOSIALISASI DAN PEMBINAAN PERSIAPAN AKREDITASI SMP NEGERI 18 MALUKU TENGAH - Fransheine Rumtutuly; Sigit Sugiarto; Lestari Lestari; Asmirani Alam; Edy Sony; Ratnah Kurniati MA; Sugian Nurwijaya; Hardiyanti Hardiyanti; Dian Rubiana Suherman; Sitti Fatimah Kamaruddin (JURNAL PENGABDIAN MANDIRI, 2023)
School accreditation is an acknowledgment and assessment by several authorized parties to assess the feasibility of an education program or unit in order to improve the quality of national education. However, knowledge about school accreditation has not been fully understood by the school because so far there has been a lack of socialization about school accreditation. Knowledge about school/madrasah accreditation is still minimal among teachers and education staff at SMP Negeri 18 Central Maluku. Therefore, community service activities were held in the form of socialization programs and coaching for teachers and education staff regarding school/madrasah accreditation at SMP Negeri 18 Central Maluku so that they would better understand the concept of accreditation, accreditation tools, and preparations for visitation. Participants in community service activities are school principals, teachers, education staff, and school and community committees. The socialization and coaching program on School/Madrasah Accreditation at SMP Negeri 18 Central Maluku can provide an understanding of the concept of accreditation, accreditation tools, and preparations for visitations for school principals, teachers, education staff, committees, and the community.